2019
DOI: 10.3390/s19184008
|View full text |Cite
|
Sign up to set email alerts
|

A Container-Attachable Inertial Sensor for Real-Time Hydration Tracking

Abstract: Various sensors have been proposed to address the negative health ramifications of inadequate fluid consumption. Amongst these solutions, motion-based sensors estimate fluid intake using the characteristics of drinking kinematics. This sensing approach is complicated due to the mutual influence of both the drink volume and the current fill level on the resulting motion pattern, along with differences in biomechanics across individuals. While motion-based strategies are a promising approach due to the prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The unit was attached at 5% of the total height below the knee joint. Acceleration values were used to calculate the angle of the lower body with regard to the vertical line, which was regarded as an estimate of the ankle angle, using the following equation (Griffith et al, 2019;Kim & Hwang, 2018):…”
Section: Apparatusmentioning
confidence: 99%
“…The unit was attached at 5% of the total height below the knee joint. Acceleration values were used to calculate the angle of the lower body with regard to the vertical line, which was regarded as an estimate of the ankle angle, using the following equation (Griffith et al, 2019;Kim & Hwang, 2018):…”
Section: Apparatusmentioning
confidence: 99%
“…The unit was attached at 5% of the total height below the knee joint. Acceleration values were used to calculate the angle of the lower body with regard to the vertical line, which was regarded as an estimate of the ankle angle, using the following equation [14], [27]:…”
Section: Apparatusmentioning
confidence: 99%
“…They found that using kNN to classify drink events achieved F1-score of 89.92% for detecting a drink event within a window and 85.88% to detect the exact frame in 11 participants. Dong et al and Griffith et al placed an elastic band with an accelerometer around a water bottle to estimate volume intake and fill ratio (fill level as a percentage of the height of the container), shown in the schematic in Figure 4 a [ 120 , 121 , 122 , 123 , 124 ]. They obtained an overall MAPE of greater than 7.64% for the fill ratio and 19.49% per sip using machine learning [ 120 , 121 , 122 ].…”
Section: Smart Containersmentioning
confidence: 99%
“… Schematic diagram of various sensor layouts for each smart container category, namely ( a ) inertial [ 120 , 121 , 122 , 123 , 124 ], ( b ) load and pressure [ 125 ], ( c ) capacitive [ 126 ], ( d ) conductive [ 127 ], ( e ) Wi-Fi [ 128 ], ( f ) vibration [ 129 ], ( g ) acoustic [ 130 ], ( h ) and other level sensor [ 131 ]. …”
Section: Figurementioning
confidence: 99%